Musa paradisiaca var sapientum fruit peel for suppression of aflatoxin producing Aspergillus spp. on groundnuts - SHARMA*, ANKITA; SHARMA, KANIKA (Indian Phytopathology, 2011)
The study represents the antifungal efficacy of aqueous extract of Musa paradisiaca fruit peel powder againstaflatoxin producing strains of Aspergillus flavus and Aspergillus parasiticus. Fungal species were isolated from infected maizeand groundnut seeds and antifungal screening was done by poisoned food technique. Inhibitory action of the extract wasconcentration dependent. Minimum inhibitory concentration (MIC) was found to be 20 mg/ml for A. flavus and 17.5 mg/ml forA. parasiticus. 35mg/ml concentration of extract was fungicidal for both test fungi whereas 45 mg/ml of extract preventedinfection of stored ground nut seeds in vivo from both test fungi. Germination of peanuts was unaffected by the applicationof extract which suggest that the extract was non phytotoxic. The results obtained in this study clearly suggest the possibleuse of fruit peel powder as ecofriendly herbal fungitoxicant to prevent biodeterioration of stored grains.